The Toxicity Phenomenon and the Related Occurrence in Metal and Metal Oxide Nanoparticles: A Brief Review From the Biomedical Perspective - Attarilar, Shokouh; Yang, Jinfan; Ebrahimi, Mahmoud; Wang, Qingge; Liu, Jia; Tang, Yujin; Yang, Junlin (Frontiers in Bioengineering and Biotechnology, 2020)
Thousands of different nanoparticles (NPs) involve in our daily life with various origins from food, cosmetics, drugs, etc. It is believed that decreasing the size of materials up to nanometer levels can facilitate their unfavorable absorption since they can pass the natural barriers of live tissues and organs even they can go across the relatively impermeable membranes. The interaction of these NPs with the biological environment disturbs the natural functions of cells and its components and cause health issues. In the lack of the detailed and comprehensive standard protocols about the toxicity of NPs materials, their control, and effects, this review study focuses on the current research literature about the related factors in toxicity of NPs such as size, concentration, etc. with an emphasis on metal and metal oxide nanoparticles. The goal of the study is to highlight their potential hazard and the advancement of green non-cytotoxic nanomaterials with safe threshold dose levels to resolve the toxicity issues. This study supports the NPs design along with minimizing the adverse effects of nanoparticles especially those used in biological treatments.